Crystal structure of poly[diaqua-(μ8-1,1′:2′,1′′-terphenyl-3,3′′,4′,5′-tetracarboxylato-κ8O1:O2:O3:O4:O5:O6:O7:O8)dicopper(II)], C22H14Cu2O10 - Li Wenjun; Mai Si Lang Jiu (Zeitschrift für Kristallographie - New Crystal Structures, 2019)
C22H14Cu2O10, orthorhombic, Pccn (no. 56), a = 8.7989(3) Å, b = 10.4284(3) Å, c = 23.6873(6) Å, V = 2173.51(11) Å3, Z = 8, Rgt(F) = 0.0398, wRref(F2) = 0.0969, T = 293(2) K.